Amalgameted tin mines of Nigeria Limited : twenty- eight annual report and accounts for the year ended 31st March 1967 (London : Amalgamated tin mines of Nigeria, 1967)
This is the annual report of the general meeting of the members of Amalgamated tin mines of Nigeria Limited held in London 10th day of November, 1967 in London.
ahz 18/04/2019
Loans
Keywords: Tin; Mining; Nigeria